A comparative study of PVDF hollow fiber membranes for the treatment of refinery produced wastewater - Erna Yuliwati, 1967-, author; Ahmad Fauzi Ismail, 1966-, author; International Conference on Membrane Science and Technology (7th : Kuala Lumpur, Malaysia : 2009) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL